Enhancing the effectiveness of acute respiratory tract infection control program of BRAC - Kamal, Firoz Mahboob (BRAC Research and Evaluation Division (RED), 2019)
This study was aimed at evaluating the Acute RespiratOr')' Tract Infection (ARI) Control Program of BRAC (Bangladesh Rural Advancement Committee - the largest NGO in Bangladesh) with the purpose of enhancing its effectiveness. So, along with diagnostic deliberation. problem solving has been a major imperative of the study. In the health care sector in Bangladesh, the strategic management issues enjoy little attention. Most emphases are usually spent to establish sophisticated hospital with huge physical infra-structures focused to an urban clientele. Even in its impoverished economy, large hospitals are not few. But a great irony is that severai thousands of beds in these hospitals lie vacant or not utilized. This situation is not only because of inadequate amenities in state-run hospitals, rather largely owes to lack of strategic management. Previously the sector was run on charity or public funds granted by the altruistic motive of the government, so its financial sustainability Oi competitive positioning in the market were not perceived as a worthy concern. But now, the global economic constraints as well as competitive health care initiatives of some entrepreneurial genius have crept into this domain df charity and altruism. The health care sector is now called the 'health care industry' - especially in developed countries. so the competitive positioning of a health program essentially becomes crucial in present day perspectives. In USA, health care went from S 11.5 billion in 1960 and the tenth largest portion of economy to near1y S 1 trillion in 1995 - only second in size to real estate ( Duncan et al., 1995). Due to such rapid boom in this sector, strategic thinking, strategic planning and strategic management of health care industry have attained the pick of importance now-a-days. The ARI control program of BRAC is funded by donors. The program can not continue relying on donations. hence can not help BRAC fulfill its mission of serving the rural people in the long run. Therefore its strategic planning and management are crucial not only for its .effective functioning but for self-reliance. In Bangladesh, the formal health care sector does very little for the rural majority, it seldom stretches out beyond the country's urban boundary. The rural poor are still dependent on. indeed hostage to, quacks and untrained practitioners. In this context. BRAC's ARI control program has to compete for patients. mar1<ets, revenues, employees and more; and as such needs competitive strengths to be successful and sustainable. This report, though restricted in its deliberation by much constraints, has been focused on addressing those issues with a view at positioning the program as an effective caregiver - both at present and in the future. So in this report. emphasis will be on strategic planning component more so than on conventional evaluation analysis.